2019
DOI: 10.1177/0309364618789449
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic characterisation of Össur Flex-Run prosthetic feet for a more informed prescription

Abstract: A better understanding of dynamic characteristics of the feet can help tune the feet to the user's requirements in promoting a better gait performance. Clinical relevance The dynamic data determined from this study are needed to better inform the amputees in predicting the natural frequency of the foot prescribed. The amputees can intuitively tune the cyclic body rhythm during walking or running to match with the natural frequency. This could eventually promote a better gait performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Mechanical tests showed that the system was durable enough to withstand maximum tibial acceleration (2 g) when walking over enough cycles to meet ISO 22657 requirements [53,54]. It was also tested for natural resonance frequencies based on ISO 7626-5:2019 while keeping in mind the natural frequencies of running and walking [55,[57][58][59]. The system did not have any resonance frequencies between 0.1 and 10 Hz which includes low frequency walking as well as running frequencies which average around 4.1 Hz [55].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical tests showed that the system was durable enough to withstand maximum tibial acceleration (2 g) when walking over enough cycles to meet ISO 22657 requirements [53,54]. It was also tested for natural resonance frequencies based on ISO 7626-5:2019 while keeping in mind the natural frequencies of running and walking [55,[57][58][59]. The system did not have any resonance frequencies between 0.1 and 10 Hz which includes low frequency walking as well as running frequencies which average around 4.1 Hz [55].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies involve modelling the behaviour of the blade to better represent the experimental results. They use parametric modelling 13,14 , finite element modelling 15 , or biomechanical models 16 . The simplest modelling for RSPs is the same as the one used for modelling the leg during the running or walking stance phase: namely the spring-mass model 17,18 .…”
Section: Figure 1 (A)mentioning
confidence: 99%
“…Loads and frequencies change between running and ambulation, and therefore when categorized for running, such a foot would not be optimal for everyday ambulation. 7 PHYSICAL THERAPY EVALUATION Initial evaluation by a physical therapist specializing in running medicine revealed hip extension strength deficits bilaterally, with the involved right leg exhibiting 4-/5 strength and sound left limb with 4/5 strength. Hip abduction muscle strength was 4/5 bilaterally.…”
Section: Prosthesis Designmentioning
confidence: 99%